Pembelajaran Daring Berbasis Proyek Terhadap Kemampuan Berpikir Kreatif Pada Mahasiswa Universitas Muslim Maros - Pertiwi Indah Lestari; Ernawati Ernawati (Universitas Negeri Makassar, 2022)
This study aims to determine the effectiveness of project-based online learning on students' creative thinking skills in waste management courses. The type of research used is quantitative research with the Pre-Experiment method with a one shot case study design. The subjects of this study were 23 students of biology study program Muslim University Of maros who were given treatment in the learning process and the results were observed. The instrument of this research is a test of student learning outcomes to measure students' creative abilities and student response questionnaires. The data analysis technique used is quantitative data analysis, to determine the effectiveness of the applied learning model, it can be seen from the quality of student test results and data from student responses in the learning process. The percentage of achievement of student learning outcomes is in the high and very high categories, amounting to 95.6%, which is greater than the effective criteria at 75%. The percentage of positive responses from students is 97%. This shows that the project-based online learning model is effectively used in waste management learning